Hubungan Usia dengan Kepatuhan Minum Obatantihipertensi di Puskesmas Tanjung Pinang Kota Jambi Tahun 2024 - Anggun Suci Otriyani; Sabarudin, Sabarudin; Supriadi, Supriadi; Hisran, Hisran; Rahmah, Rahmah (Yayasan Literasi Sains Indonesia, 2024)
Hypertension is one of the most common diseases in Indonesia. If this disease is not treated properly, it can cause complications of other diseases. To avoid these complications, patients must take drugs correctly in their treatment. One of the factors that affect the treatment of hypertension is compliance in taking antihypertensive drugs. The purpose of this study was to determine the relationship between age group and adherence to taking antihypertensive medication at the Tanjung Pinang Health Center, Jambi City in 2024. This study used a cross sectional method using the MMAS-8 (Morisky Adherence Scale) questionnaire instrument by taking a sample of hypertensive patients in the elderly category who were patients referred back to the Tanjung Pinang Health Center. Primary data by distributing questionnaires to patients who seek treatment. The population in this study amounted to 347 elderly hypertensive patients. Sampling using purposive sampling. With a sample of 78 respondents. The results were obtained based on the percentage of low compliance as many as 32 respondents (41.0%), moderate compliance as many as 27 respondents (34.6%) and the high compliance category as many as 19 respondents (24.4%). For the age category in the early elderly with moderate compliance as many as 14 respondents (53.8%), late elderly high compliance as many as 7 respondents (26.9%) and seniors low compliance as many as 17 respondents (6.4%). Based on the chi square test that has been carried out, the p value is 0.011 <0.05, which indicates that there is a significant relationship between age and compliance with taking antihypertensive drugs at the Tanjung Pinang Health Center, Jambi City in 2024. To improve compliance in taking medication, it is hoped that health workers can increase the provision of health education, counseling, motivation and encouragement to people with hypertension to always be obedient in taking medication and managing a healthy lifestyle for their recovery.